2021
DOI: 10.3389/fcell.2021.637248
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood-Derived Exosomes From Very Preterm Infants With Bronchopulmonary Dysplasia Impaired Endothelial Angiogenesis: Roles of Exosomal MicroRNAs

Abstract: Premature infants have a high risk of bronchopulmonary dysplasia (BPD), which is characterized by abnormal development of alveoli and pulmonary vessels. Exosomes and exosomal miRNAs (EXO-miRNAs) from bronchoalveolar lavage fluid are involved in the development of BPD and might serve as predictive biomarkers for BPD. However, the roles of exosomes and EXO-miRNAs from umbilical cord blood of BPD infants in regulating angiogenesis are yet to be elucidated. In this study, we showed that umbilical cord blood-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 48 publications
5
47
0
Order By: Relevance
“…These two miRNAs were involved in the pulmonary vasculature and pulmonary hypertension and intrauterine growth restriction [116,117], which are closely associated with BPD. A more recent study found that umbilical cord blood-derived exosomal miRNAs from very preterm human infants with BPD were 90 downregulated (e.g., miR-103a-3p and miR-185-5p) and 328 upregulated (e.g., miR-200a-3p), which were associated with PI3K/Akt and angiogenesis-related signaling pathways [98]. Further, overexpression of miR-103a-3p and miR-185-5p augmented endothelial cell proliferation, migration and tube formation, while overexpression of miR-200a-3p impeded these angiogenic responses [98].…”
Section: Epigenetic Programming and Neonatal Chronic Lung Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…These two miRNAs were involved in the pulmonary vasculature and pulmonary hypertension and intrauterine growth restriction [116,117], which are closely associated with BPD. A more recent study found that umbilical cord blood-derived exosomal miRNAs from very preterm human infants with BPD were 90 downregulated (e.g., miR-103a-3p and miR-185-5p) and 328 upregulated (e.g., miR-200a-3p), which were associated with PI3K/Akt and angiogenesis-related signaling pathways [98]. Further, overexpression of miR-103a-3p and miR-185-5p augmented endothelial cell proliferation, migration and tube formation, while overexpression of miR-200a-3p impeded these angiogenic responses [98].…”
Section: Epigenetic Programming and Neonatal Chronic Lung Diseasementioning
confidence: 99%
“…A more recent study found that umbilical cord blood-derived exosomal miRNAs from very preterm human infants with BPD were 90 downregulated (e.g., miR-103a-3p and miR-185-5p) and 328 upregulated (e.g., miR-200a-3p), which were associated with PI3K/Akt and angiogenesis-related signaling pathways [98]. Further, overexpression of miR-103a-3p and miR-185-5p augmented endothelial cell proliferation, migration and tube formation, while overexpression of miR-200a-3p impeded these angiogenic responses [98]. Additionally, miR-34a expression was found to be decreased in the postnatal hypoxia-induced mouse model of BPD/lung injury [101].…”
Section: Epigenetic Programming and Neonatal Chronic Lung Diseasementioning
confidence: 99%
“…Among them, hsa_circ_0086913/hsa-miR-103a-3p/transmembrane 4 L six family member 1 (TM4SF1) was predicted with a PCC of 0.93. In a recent study, the researchers found that the expression level of hsa-miR-103a-3p related to the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signaling pathway was decreased in UCB-derived exosomes from the BPD group compared with the NBPD group [ 16 ]. Further, the overexpression of hsa-miR-103a-3p in normal HUVECs significantly promoted cell proliferation, cell migration, and tube formation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers reported that exosomes played a crucial role in BPD [11][12][13], and may function through selected proteins, lipids, nucleic acids, and glycoconjugates [14,15]. In addition, a recent study demonstrated that UCB-derived exosomes of infants with BPD impair angiogenesis, potentially through differentially expressed exosomal miRNAs [16]. However, the roles of UCB-derived exosomal circular RNAs (cir-cRNAs) of infants with BPD remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that exosomes' ability to modulate endothelial cell migration decreased over time [ 82 ]. Exosomes could originate from maternal circulation and cord blood and promote endothelial cell proliferation, migration, and tube formation [ 83 ]. The activity of maternal serum-derived exosomes is higher than that of exosomes from cord blood [ 84 ].…”
Section: The Importance Of Exosomes In Pregnancy: Focus On Angiogenesismentioning
confidence: 99%